ANALISIS YURIDIS TENTANG PERLINDUNGAN HUKUM TERHADAP HEWAN PADA TINDAK PIDANA ANIMAL ABUSE DI INDONESIA - Tirza Bonita; Erdianto Effendi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Animal abuse has recently emerged and has gone viral on social media.The high number of abandoned animals also affects the number of cases of animalabuse. The factor of the Indonesian population who also does not understandabout animal cruelty makes animal abuse often occur. Many regulations relatedto animal protection are currently unknown to the public and even lawenforcement officials themselves. Weak punishment for animal abuse in theCriminal Code is an obstacle in protecting the animals around us. Therefore,legal protection for animals in the crime of animal abuse is needed to reform toenforce the law and protect the existence of animals from human evil treatment ofanimals considering that animals are also living creatures that do not deserve tobe hurt.This type of research is normative juridical research, namely researchconducted by examining literature discussions with secondary data sourcesconsisting of primary legal materials in the form of laws and regulations,secondary legal materials from legal books, and tertiary legal materials in theform of dictionaries. Then the data were analyzed qualitatively, namely analyzingthe data descriptively obtained from secondary data.From the results of the study it was concluded that, first, the legalregulation of animal protection in Indonesia uses Law Number 41 of 2014concerning Animal Husbandry and Animal Health, amendments to Law Number18 of 2009 concerning Animal Husbandry and Health, Government RegulationNumber 95 of 2012 concerning Animal Husbandry and Animal Health. VeterinaryPublic Health and Animal Welfare and the Criminal Code. Article 302 forimposing punishment on perpetrators of criminal acts of animal abuse is Article302, which has a weak sentence and the sanctions do not provide a deterrenteffect to perpetrators of criminal acts of animal abuse. Second, the urgency ofrenewing regulations to protect animals from criminal acts of abuse is needed, toprotect animals from persecution and until now new rules regarding animalprotection are currently contained in the RKUHP which it is not yet known whenit will be ratified.Keywords: Analysis-Legal Protection-Animal-Criminal-Abuse